PENGOLAHAN LIMBAH CANGKANG TIRAM MENJADI PASTA GIGI DI DESA ALUE NAGA, BANDA ACEH - Irwan Irwan; Taufiqi Hidayatullah; Sayyid Afdhal El Rahim; Eli Nurliza; Nurul Azmi; Dedi Fazriansyah Putra; Ilham Zulfahmi (Jurnal Abdi Insani, 2023)
Alue Naga Village is one of the villages in the Syiah Kuala sub-district of Banda Aceh City. Most of the community works as oyster finders and sellers to fulfill the economy. The large number of oysters cultivated and the results of conventional searches cause oyster shell waste to increase and provide environmental problems. One form of processing oyster shells into economic products while providing added value in improving the community's economy is toothpaste. The purpose of implementing this service activity is to provide knowledge and skills to the community in processing oyster shells into toothpaste. This oyster shell processing activity was carried out with a group of oyster farmers from July to September. The method of implementing activities includes socialization, dental health counseling, and training and assistance in making toothpaste for partners and evaluating the results. The results of the implementation of this community service activity show that dental health counseling has an impact on increasing community knowledge. In addition to the product analysis results, the community likes toothpaste's, shape, texture, and color. The color appearance of the toothpaste produced is green and has a pH of 7. The pH value obtained from this toothpaste product meets the quality requirements (SNI 12-3524-1995). Based on the results of this activity, it can be concluded that the community gained new knowledge and skills in processing oyster shells as toothpaste.